Estimating earthquake magnitudes induced by active faults: Bayesian approach - Min-Hao Wu; Jui-Pin Wang; J. Bruce H. Shyu; Su-Chin Chang; Chia-Ying Sung (Geoscience Letters)
Abstract The magnitude of major earthquakes induced by active faults is essential to seismic hazard analysis. However, the sample size of such earthquakes recorded by the accurate, modern instrumentation is minimal. Hence, the estimate using the (conventional) Frequentist method only based on samples/observations becomes less specific. Like other applications of the Bayesian approach that integrates (limited) observation and prior information, this paper introduces a new one for estimating the magnitude of major earthquakes induced by an active fault. In addition to the Bayesian algorithm, two case studies were also presented in this paper.